Answer:
Multiply he second equation by -3
The solution is (0, 2)
Explanation:
When doing this, you make it so you can eliminate the x variables...
start with
3x + 6y = 12
x + 5y = 10
Now multiply the second equation by -3
-3(x + 5y = 10) becomes...
-3x - 15y - 30
Now our system is
3x + 6y = 12
-3x - 15y = -30
When we add them together, we get
-9y = -18
***The x variable is gone, so we have eliminated that
Here is the final solution in case you need it..
-9y = -18 solve for y..
y = 2 (divide by -9 on both sides to isolate y)
There for x is
x + 5(2) = 10
x + 10 = 10
x = 0
so the solution is (0, 2)